Edukasi Pencegahan Prolaps Organ Panggul Pasca Kehamilan dan Persalinan: Program Kemitraan Masyarakat - Kurniawati, Eighty Mardiyan; Hardianto, Gatut; Wahyuningtyas, Riska; Rahmawati, Nur Anisah; Mustofa, Vina Firmanty; Safitri, Cahyani Tiara; Kurniawan, Agde Muzaky; Mardianti, Mardianti (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction:Pelvic organ prolapse is the descent of the pelvic structure into the vagina due to weakness of the ligaments or muscles. This complication can affect the quality of life of women in the future. One of the risk factors is related to pregnancy and childbirth. The health center is one of the health facilities that meet and make initial contact with pregnant women. Objective: This community service aims to empower health workers in preventing pelvic organ prolapse as a long-term impact that is at risk of occurring due to the physiological process of pregnancy and childbirth so that it can contribute to improving the quality of life of mothers. Method: This public service was conducted by the community service team from Universitas Airlangga on October 5, 2024, involving 27 pregnant women and 10 healthcare workers. The activities were designed to be participatory. Evaluation was carried out by providing pretests and posttests to pregnant women and health workers. Result: The activities carried out were providing materials on the introduction of Pelvic Organ Prolapse (POP), risk factors for POP related to pregnancy and childbirth, the impact of POP on women's quality of life, prevention of POP during pregnancy and childbirth, family support, and management if POP has occurred. The average pretest score was 76.00 (SD ± 5.2), while the average posttest score increased to 78.00 (SD ± 4.8). Statistical analysis indicated a significant increase in knowledge before and after the educational intervention (p < 0.05). Conclusion: The community partnership program proved effective in increasing participants' knowledge. It is recommended that this program be carried out regularly and expanded in scope to reach a broader audience, enhancing awareness and understanding of POP, particularly among pregnant women and healthcare workers.